Processing Math: Done
To print higher-resolution math symbols, click the
Hi-Res Fonts for Printing button on the jsMath control panel.

jsMath

Lösung 3.4:4

Aus Online Mathematik Brückenkurs 2

(Unterschied zwischen Versionen)
Wechseln zu: Navigation, Suche
K (Lösning 3.4:4 moved to Solution 3.4:4: Robot: moved page)
Zeile 1: Zeile 1:
-
{{NAVCONTENT_START}}
+
Because
-
<center> [[Image:3_4_4.gif]] </center>
+
<math>z=\text{1}-\text{2}i</math>
-
{{NAVCONTENT_STOP}}
+
should be a root of the equation, we can substitute
 +
<math>z=\text{1}-\text{2}i</math>
 +
in and the equation should be satisfied:
 +
 
 +
 
 +
<math>\left( \text{1}-\text{2}i \right)^{3}+a\left( \text{1}-\text{2}i \right)+b=0</math>
 +
 
 +
 
 +
We will therefore adjust the constants
 +
<math>a</math>
 +
and
 +
<math>b</math>
 +
so that the relation above holds. We simplify the left-hand side,
 +
 
 +
 
 +
<math>-11+2i+a\left( \text{1}-\text{2}i \right)+b=0</math>
 +
 
 +
 
 +
and collect together the real and imaginary parts:
 +
 
 +
 
 +
<math>\left( -11+a+b \right)+\left( 2-2a \right)i=0</math>
 +
 
 +
 
 +
If the left-hand side is to equal the right-hand side, the left-hand side's real and imaginary parts must be equal to zero, i.e.
 +
 
 +
 
 +
 
 +
<math>\left\{ \begin{array}{*{35}l}
 +
-11+a+b=0 \\
 +
2-2a=0 \\
 +
\end{array} \right.</math>
 +
 
 +
 
 +
This gives
 +
<math>a=\text{1}</math>
 +
and
 +
<math>b=\text{1}0</math>.
 +
 
 +
The equation is thus
 +
 
 +
 
 +
<math>z^{2}+z+10=0</math>
 +
 
 +
 
 +
and has the prescribed root
 +
<math>z=\text{1}-\text{2}i</math>.
 +
 
 +
What we have is a polynomial with real coefficients and we therefore know that the equation has, in addition, the complex conjugate root
 +
<math>z=\text{1}+\text{2}i</math>.
 +
 
 +
Hence, we know two of the equation's three roots and we can obtain the third root with help of the factor theorem. According to the factor theorem, the equation's left-hand side contains the factor
 +
 
 +
 
 +
<math>\left( z-\left( 1-2i \right) \right)\left( z-\left( 1+2i \right) \right)=z^{2}-2z+5</math>
 +
 
 +
 +
and this means that we can write
 +
 
 +
 
 +
<math>z^{3}+z+10=\left( z-A \right)\left( z^{2}-2z+5 \right)</math>
 +
 
 +
 
 +
where
 +
<math>z-A</math>
 +
is the factor which corresponds to the third root
 +
<math>z=A</math>. Using polynomial division, we obtain the factor
 +
 
 +
 
 +
<math>\begin{align}
 +
& z-A=\frac{z^{3}+z+10}{z^{2}-2z+5} \\
 +
& =\frac{z^{3}-2z^{2}+5z+2z^{2}-5z+z+10}{z^{2}-2z+5} \\
 +
& =\frac{z\left( z^{2}-2z+5 \right)+2z^{2}-4z+10}{z^{2}-2z+5} \\
 +
& =z+\frac{2z^{2}-4z+10}{z^{2}-2z+5} \\
 +
& =z+\frac{2\left( z^{2}-2z+5 \right)}{z^{2}-2z+5} \\
 +
& =z+2 \\
 +
\end{align}</math>
 +
 
 +
 
 +
Thus, the remaining root is
 +
<math>z=-\text{2}</math>.

Version vom 13:32, 28. Okt. 2008

Because z=12i should be a root of the equation, we can substitute z=12i in and the equation should be satisfied:


12i3+a12i+b=0 


We will therefore adjust the constants a and b so that the relation above holds. We simplify the left-hand side,


11+2i+a12i+b=0 


and collect together the real and imaginary parts:


11+a+b+22ai=0 


If the left-hand side is to equal the right-hand side, the left-hand side's real and imaginary parts must be equal to zero, i.e.


11+a+b=022a=0 


This gives a=1 and b=10.

The equation is thus


z2+z+10=0


and has the prescribed root z=12i.

What we have is a polynomial with real coefficients and we therefore know that the equation has, in addition, the complex conjugate root z=1+2i.

Hence, we know two of the equation's three roots and we can obtain the third root with help of the factor theorem. According to the factor theorem, the equation's left-hand side contains the factor


z12iz1+2i=z22z+5 


and this means that we can write


z3+z+10=zAz22z+5 


where zA is the factor which corresponds to the third root z=A. Using polynomial division, we obtain the factor


zA=z22z+5z3+z+10=z22z+5z32z2+5z+2z25z+z+10=z22z+5zz22z+5+2z24z+10=z+z22z+52z24z+10=z+z22z+52z22z+5=z+2


Thus, the remaining root is z=2.